(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Asset management in educational institutions is still largely manual, potentially leading to recording errors, reporting delays, and weak oversight of facilities and infrastructure. This study aims to evaluate and synthesize previous research findings related to the implementation of a QR code-based asset inventory system in the educational context. The study used a Systematic Literature Review (SLR) approach to 25 articles published between 2015 and 2026 and indexed in Scopus, ScienceDirect, Google Scholar, and Sinta. Data analysis was conducted through the stages of identification, screening, and eligibility of the literature, followed by thematic coding and narrative synthesis to group the main research findings. The results of the study indicate that the QR code-based inventory system is effective in reducing recording errors, accelerating the asset verification process, and increasing transparency in asset management through integration with web-based platforms and lifecycle management. In addition to its administrative function, QR codes have also developed as a supporting medium for interactive learning. The main challenges identified include limited digital infrastructure, user resistance, and data security issues. This study concludes that a QR code-based asset inventory system is an efficient and relatively low-cost solution for modern educational asset management.